Democratic Republic of Sao Tome and Principe : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2006)
The paper reviews the background and the existing institutional framework for oil sector development in Sao Tome and Principe and the challenges faced in implementing transparency rules in all oil-related transactions. It provides a quantitative analysis of the impact of oil sector development on government receipts, spending, and savings, and discusses the determinants of inflation from a statistical point of view. It also shows an analysis of the weak relationship between money growth and inflation.